2020
DOI: 10.3389/fimmu.2019.03059
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 Counteracts Neuropathic Pain Development Through Induction of IL-10

Abstract: Neuroimmune-glia interactions have been implicated in the development of neuropathic pain. Interleukin-27 (IL-27) is a cytokine that presents regulatory activity in inflammatory conditions of the central nervous system. Thus, we hypothesized that IL-27 would participate in the neuropathic pain process. Here, we found that neuropathic pain caused by peripheral nerve injury (spared nerve injury model; SNI), was enhanced in IL-27-deficient (−/−) mice, whereas nociceptive pain is similar to that of wild-type mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…For instance, we recently found that at the level of sensory ganglia there is an increase in the production of IL-27 which plays a regulatory role in the development of neuropathic pain. 52 We also showed that Il-27 counteracts neuropathic pain by acting on its receptor expressed by sNAMs that in turn stimulate the production of the antinociceptive cytokine IL-10. 52 …”
Section: Mechanisms Of Sensory Neuron–associated Macrophages Activation and Accumulation After Nerve Injurymentioning
confidence: 76%
See 1 more Smart Citation
“…For instance, we recently found that at the level of sensory ganglia there is an increase in the production of IL-27 which plays a regulatory role in the development of neuropathic pain. 52 We also showed that Il-27 counteracts neuropathic pain by acting on its receptor expressed by sNAMs that in turn stimulate the production of the antinociceptive cytokine IL-10. 52 …”
Section: Mechanisms Of Sensory Neuron–associated Macrophages Activation and Accumulation After Nerve Injurymentioning
confidence: 76%
“…Concomitantly to the production of pronociceptive molecules by immune and glial cells across the pain pathway (local of injury; sensory ganglia, and spinal cord) after peripheral nerve injury, there is also evidence suggesting the production of anti-inflammatory/antinociceptive molecules. 3 , 5 , 14 , 20 , 22 , 52 , 85 , 144 , 145 , 168 , 229 In this context, increasing evidence suggests that peripheral macrophages also play an important role in the resolution of chronic pain. 25 , 39 The identification of these regulatory mechanisms in peripheral macrophages that counteract neuropathic pain would also reveal novel targets for its treatment.…”
Section: Mechanisms Of Sensory Neuron–associated Macrophages Activation and Accumulation After Nerve Injurymentioning
confidence: 99%
“…Reversely, M2 macrophages produce antiinflammatory cytokine IL-10. The enhancement of IL-10 expression or inhibition of M1 macrophages could attenuate or abolish the neuropathic pain state (Kiguchi et al, 2017;Fonseca et al, 2019;Iwasa et al, 2019). Schwann cells are important glial cells in the peripheral nervous system, which act as insulators of axons.…”
Section: Peripheral Sensitizationmentioning
confidence: 99%
“…Actually, immune cells express inflammation modulatory factors (e.g., IL-10 and IL-27) during different phases of HIV infection (Soare et al, 2019). IL-27 receptor, expressed by macrophage, microglia, and astrocytes of the sensory ganglia and spinal cord, its activation has the function of counteracting neuropathic pain (Fonseca et al, 2019). Therefore, both pro-inflammation and anti-inflammation are processing simultaneously between immune cells.…”
Section: Future Perspectivementioning
confidence: 99%
“…IL-27 and IL-35 are structurally different (heterodimeric cytokines) to the original members, however still considered a part of the IL-6 superfamily. Genetic ablation of IL-27 was shown to deprive mice of an innate IL-10-dependent antinociceptive reaction in a nerve injury model [ 664 ]. IL-27 acts anti-inflammatory, limiting thermal and mechanical sensation, as mice lacking IL-27 or its receptor spontaneously showed chronic pain-like hypersensitivity, with reversal of the behaviors upon recombinant IL-27 injection [ 665 ].…”
Section: Immune Reactionmentioning
confidence: 99%